Hepatic GRK2 is dispensable for glucose homeostasis and other key metabolic parameters in mice - Antwi-Boasiako Oteng; Srinivas Pittala; Andrea Kliewer; Yishu Qiu; Jürgen Wess (Elsevier, 2024)
Objective: G-protein-coupled receptor (GPCR) kinases (GRKs) abrogate GPCR signaling by promoting receptor desensitization and internalization. Accumulating evidence suggests that GRK2 represents an important regulator of GPCR-mediated effects on systemic glucose metabolism, obesity, and insulin resistance. Despite the key role of the liver in maintaining euglycemia, the potential metabolic relevance of hepatic GRK2 has yet to be examined. Thus, the goal of this study was to explore the potential role of hepatic GRK2 in maintaining glucose homeostasis and other key metabolic functions. Methods: To address this question, we generated mice that showed a ∼90% reduction in GRK2 protein expression selectively in hepatocytes (Hep-GRK2-KO mice) and subjected these mice, together with their control littermates, to systematic metabolic phenotyping studies. Results: We found that Hep-GRK2-KO mice maintained on regular chow did not differ significantly from their control littermates in glycemia, glucose tolerance, insulin sensitivity, in vivo gluconeogenesis, and glucagon-induced hyperglycemia. We obtained similar findings when we analyzed Hep-GRK2-KO mice and control littermates consuming an obesogenic high-fat diet. Likewise, plasma levels of insulin, glucagon, free fatty acids, and ketone bodies remained unaffected by the lack of hepatocyte GRK2. The same was true when we examined the expression levels of key genes regulating hepatic glucose and fatty acid metabolism. Conclusion: In summary, our data suggest that hepatocyte GRK2 is dispensable for systemic glucose homeostasis and other key metabolic functions in both lean and obese mice. This finding suggests that drug development efforts aimed at inhibiting GRK2 to improve impaired glucose homeostasis and insulin sensitivity need to focus on other metabolically important tissues.